A multidisciplinary approach to the management of fibrolamellar carcinoma: current perspectives and future prospects - Polychronidis, Georgios; Murtha-Lemekhova, Anastasia; Fuchs, Juri; Karathanasi, Evdokia; Hoffmann, Katrin (OncoTargets and therapy, 2022)
Management of fibrolamellar carcinoma
Gesehen am 14.12.2022